Case studies of the expansion of Acacia dealbata in the valley of the river Miño (Galicia, Spain) - Antonio Vazquez de la Cueva (Forest Systems, 2014)
Aim of study: Acacia dealbata is a naturalized tree of invasive behaviour that has expanded from small plots associated with vineyards into forest ecosystems. Our main objective is to find evidence to support the notion that disturbances, particularly forest fires, are important driving factors in the current expansion of A. dealbata. Area of study: We mapped it current distribution using three study areas and assesses the temporal changes registered in forest cover in these areas of the valley of the river Miño. Material and Methods: The analyses were based on visual interpretation of aerial photographs taken in 1985 and 2003 of three 1x1 km study areas and field works. Main result: A 62.4%, 48.6% and 22.2% of the surface area was covered by A. dealbata in 2003 in pure or mixed stands. Furthermore, areas composed exclusively of A. dealbata make up 33.8%, 15.2% and 5.7% of the stands. The transition matrix analyses between the two dates support our hypothesis that the areas currently covered by A. dealbata make up a greater proportion of the forest area previously classified as unwooded or open forest than those without A. dealbata cover. Both of these surface types are the result of an important impact of fire in the region. Within each area, A. dealbata is mainly located on steeper terrain, which is more affected by fires. Research highlights: A. dealbata is becoming the dominant tree species over large areas and the invasion of this species gives rise to monospecific stands, which may have important implications for future fire regimes. Keywords: Fire regime; Mimosa; plant invasion; silver wattle.